To Trust or to Monitor: A Dynamic Analysis - HUANG, Fali (Institutional Knowledge at Singapore Management University, 2007)
In a principal-agent framework, principals can mitigate moral hazard problems not only through extrinsic incentives such as monitoring, but also through agents’ intrinsic trustworthiness. Their relative usage, however, changes over time and varies across societies. This paper attempts to explain this phenomenon by endogenizing agent trustworthiness as a response to potential returns. When monitoring becomes relatively cheaper over time, agents acquire lower trustworthiness, which may actually drive up the overall governance cost in society. Across societies, those giving employees lower weights in choosing governance methods tend to have higher monitoring intensities and lower trust. These results are consistent with the empirical evidence.